The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/adhm.202203391
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of M2 Macrophages‐Derived Exosomes via Click Chemistry for Spinal Cord Injury Repair

Abstract: Spinal cord injury (SCI) is one of the most common causes of death and disability. The effective modulation of complicated microenvironment, regeneration of injured spinal cord tissue, and the functional recovery after SCI are still clinical challenges. Recently, macrophages‐derived exosomes have shown great potential for various diseases due to their inflammation‐targeting property. However, further modifications are needed to endow exosomes with the neural regenerative potential for SCI recovery. In the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Clinical evidences disclose that many macrophages are significantly increased in IDs patients with the inflammatory tissue. [ 73 ] Macrophages have many phenotypes, and the balance of different phenotypes plays an essential role in the inflammatory cascade, mainly divided into M0 (resting state), M1, and M2 phenotypes. [ 74 ] The M1 phenotype secretes inflammatory cytokines, accelerating oxidative processes and inhibiting tissue repair.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical evidences disclose that many macrophages are significantly increased in IDs patients with the inflammatory tissue. [ 73 ] Macrophages have many phenotypes, and the balance of different phenotypes plays an essential role in the inflammatory cascade, mainly divided into M0 (resting state), M1, and M2 phenotypes. [ 74 ] The M1 phenotype secretes inflammatory cytokines, accelerating oxidative processes and inhibiting tissue repair.…”
Section: Resultsmentioning
confidence: 99%
“…The immunostaining analysis of the 200 kDa subunit of neurofilament (NF200), a marker protein of axon, was employed to evaluate the axonal regeneration. [ 61 ] Moreover, barriers created by scar‐forming astroglia have been proposed to be the primary causes of axon regeneration failure after SCI. [ 71 ] Thus, glial fibrillary acidic protein (GFAP) expression was employed as a marker of astrogliosis.…”
Section: Resultsmentioning
confidence: 99%
“…Promoting the transition of microglia from M1 to M2 type is considered an important therapeutic target for improving the neurological outcome of SCI. [59][60][61] Several studies have demonstrated that the CCL2-CCR2 axis played an important role in microglia activation and polarization. [62,63] In light of this, we next explored the effect of CCR2-MM@PLGA/NPs on microglia activation and polarization in vitro.…”
Section: Ccr2-mm@plga/nps Inhibitory Effect On Proinflammatory Polari...mentioning
confidence: 99%
“…In vitro experiments demonstrated that MEXI effectively attenuated inflammation by modulating macrophage activity and facilitated the differentiation of neural stem cells into neurons. Furthermore, in vivo administration of engineered exosomes via tail vein injection resulted in targeted delivery to the site of spinal cord injury ( Zeng et al, 2023a ).…”
Section: Improvement Strategies For Exosomesmentioning
confidence: 99%